DETERMINANTS OF DENTAL NURSEâS DECISION TO CONTINUE THREE YEARS DIPLOMA THROUGH THE RECOGNITION OF PRIOR LEARNING (RPL) PROGRAM - Edi, Imam Sarwo; Suryanto, Suryanto; Triyoga, Rika Subarniati; Setyowati, Anggi (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
There are many dental nurses with vocational high school or one year diploma degree. The aim of this study was to analyze various factors that influence the decision of dental nurses with a vocational high school or one year diploma degree to continue three years diploma through the RPL program. The sample of this study was 100 dental nurses in the East Java who worked at hospital or primary health care (PUSKESMAS). This was a cross-sectional study. We used logistic Regression to analyze the data, first step was characteristic and external factor influence on decision to join RPL, second step was the effect characteristic and external factor influence on decision to join RPL amplified by psychological factors. The results showed that 1) there was an influence of characteristics on dental nursesâ decision 2) There was no influence of external factors on dental nursesâ decision. 3) Psychological factors strengthen the influence of characteristics on dental nursesâ decision and 4) Psychological factors do not strengthen the influence of external factors on dental nursesâ decision. Further research is needed to develop characteristic and psychological among dental nurse to continue three years diploma through RPL.   Keywords: Dental nurses, Education, Recognition of Prior Learning (RPL)